Aplikasi Konsep Art Education Pada Desain Komunitas Serbuk Kayu di Surabaya - Christina Ayu Paryaning Tyas (Intra, 2017)
Artists want to show art works and expression to the public. The goal is to interact and to convey the aspirations of the community. Growing Arts communities in Surabaya was not balanced by adequate space facilities. As a result, the development of the arts in particular in the field of fine art was not well appreciated by society can. The design of this art space using the case study Serbuk Kayu Communities. Serbuk Kayu community is one of the fine arts community in Surabaya. Serbuk Kayu has different fields of art group artists among others such as murals, xylography, painting, installation, video art, performance Art, literature, music, and more. This design concept is the idea of Art Education Serbuk Kayu Community are in line with the vision and mission Serbuk Kayu which is